Ferroic glasses. (December 2017) - Ji, Yuanchao; Wang, Dong; Wang, Yu; Zhou, Yumei; Xue, Dezhen; Otsuka, Kazuhiro; Wang, Yunzhi; Ren, Xiaobing
Abstract Ferroic glasses (strain glass, relaxor and cluster spin glass) refer to frozen disordered states in ferroic systems; they are conjugate states to the long-range ordered ferroic states—the ferroic crystals. Ferroic glasses exhibit unusual properties that are absent in ferroic crystals, such as slim hysteresis and gradual property changes over a wide temperature range. In addition to ferroic glasses and ferroic crystals, a third ferroic state, a glass-ferroic (i.e., a composite of ferroic glass and ferroic crystal), can be produced by the crystallization transition of ferroic glasses. It can have a superior property not possessed by its two components. These three classes of ferroic materials (ferroic crystal, ferroic glass and glass-ferroic) correspond to three transitions (ferroic phase transition, ferroic glass transition and crystallization transition of ferroic glass, respectively), as demonstrated in a generic temperature vs. defect-concentration phase diagram. Moreover, through constructing a phase field model, the microstructure evolution of three transitions and the phase diagram can be reproduced, which reveals the important role of point defects in the formation of ferroic glass and glass-ferroic. The phase diagram can be used to design various ferroic glasses and glass-ferroics that may exhibit unusual properties.